Cost-Benefit Analysis of POME Biogas Power Plant: Case Study of PLTBg Suka Damai - Donny Yoesgiantoro (Institut Teknologi Sepuluh Nopember, 2020)
Palm Oil Mill Effluent (POME) is a byproduct of processing fresh palm fruitbunches into crude palm oil (CPO) which has negative externalities in theform of gas containing methane, carbon dioxide and other greenhouse gases(GHG) which is very dangerous for environmental sustainability. The use ofpome as feedstocks for biogas power plants (PLTBg) changes the negativeexternalities of pome into positive externalities such as increasedelectrification in the area around the palm oil mill (PKS) and is good forenvironmental sustainability. PLTBg Suka Damai with a capacity of 2.4 Mwwas planned to reach the Commercial Operating Date (COD) in 2019, thefinancial calculation has a cost-benefit ratio of 1.19, percentage of InternalRate of Return (IRR) of 12.84%, percentage of weighted cost of capital(WACC) 10% and a Net Present Value (NPV) of Rp 21,275,609,209.00.Comprehending all the results, the first scenario with SCOC is the mostoptimized scenario for it provides far greater benefits to the community, fargreater than the financial revenue received by the PLTBg itself.